Global Financial Stability Report, October 2010 : Sovereigns, Funding, and Systemic Liquidity. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2010)
The global financial system is still in a period of significant uncertainty. Although the ongoing recovery is expected to gradual strengthen balance sheets, progress toward stability has experienced a setback since the April 2010 GFSR. As discussed in this October 2010 report, policymakers in many advanced countries need to confront the interactions created by slow growth, rising sovereign indebtedness, and still fragile financial institutions by addressing legacy problems in the banking system, strengthening the fundamentals of sovereign and bank balance sheets, and clarifying regulatory reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet